2008
DOI: 10.1128/jcm.00368-08
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Sequence Diversity of a Factor Required for Actin-Based Motility in Natural Populations of Burkholderia Species

Abstract: Actin-based motility of the melioidosis pathogen Burkholderia pseudomallei requires BimA. We report a high degree of conservation of bimA in 99 B. pseudomallei isolates from the area of endemicity. A geographically restricted subset of B. pseudomallei isolates harbored a B. mallei-like bimA allele (12.1%), confounding a differential diagnostic test based on amplification of species-specific bimA regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
56
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 32 publications
2
56
0
Order By: Relevance
“…Intraspecies conservation of BimA was found to be high in natural populations of B. pseudomallei, B. mallei, and B. thailandensis (19,20), with the exception that a B. mallei-like BimA variant was found in B. pseudomallei isolates restricted to the Northern Territory of Australia, but not specific multilocus sequence types (19). ClustalW alignment of predicted BimA protein sequences indicated that tandem WH2 domains predicted to mediate the binding of actin monomers were conserved in sequenced B. pseudomallei strains (19). A proline-rich motif (IP 7 ; also defined as a PRM1 motif [reviewed in reference 9]) was also conserved.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Intraspecies conservation of BimA was found to be high in natural populations of B. pseudomallei, B. mallei, and B. thailandensis (19,20), with the exception that a B. mallei-like BimA variant was found in B. pseudomallei isolates restricted to the Northern Territory of Australia, but not specific multilocus sequence types (19). ClustalW alignment of predicted BimA protein sequences indicated that tandem WH2 domains predicted to mediate the binding of actin monomers were conserved in sequenced B. pseudomallei strains (19). A proline-rich motif (IP 7 ; also defined as a PRM1 motif [reviewed in reference 9]) was also conserved.…”
mentioning
confidence: 99%
“…To identify conserved and variable portions of bimA, we previously surveyed the prevalence and sequence diversity of the gene in clinical and environmental isolates from areas of endemicity (19). Intraspecies conservation of BimA was found to be high in natural populations of B. pseudomallei, B. mallei, and B. thailandensis (19,20), with the exception that a B. mallei-like BimA variant was found in B. pseudomallei isolates restricted to the Northern Territory of Australia, but not specific multilocus sequence types (19).…”
mentioning
confidence: 99%
“…BimA is involved in actin polymerization, which is crucial for intracellular motility and intercellular spread and is thus a potential virulence factor. 12 Both patients with the B. mallei allele of bimA presented with septicemic pneumonia. While the B. mallei allele occurs in some Australian B. pseudomallei strains, Sitthidet and others 12 found none of 64 strains from across Southeast Asia harboring this allele that is present in B. mallei , the causative bacterium of glanders.…”
mentioning
confidence: 99%
“…12 Both patients with the B. mallei allele of bimA presented with septicemic pneumonia. While the B. mallei allele occurs in some Australian B. pseudomallei strains, Sitthidet and others 12 found none of 64 strains from across Southeast Asia harboring this allele that is present in B. mallei , the causative bacterium of glanders. To our knowledge the two Indian B. pseudomallei strains noted here to have the B. mallei -type bimA allele are the first B. pseudomallei isolates of Asian origin reported to contain this allele.…”
mentioning
confidence: 99%
“…Another potential problem with the BimA assays is that B. pseudomallei strains from Australia also contain the N-terminus region of BimA, indicating that the BimA tests may not be suitable for specific B. mallei differentiation from Australian B. pseudomallei isolates (Sitthidet et al, 2008). In addition, B. thailandensis-like strain MSMB43 was detected by the BimA PCR assay .…”
Section: Flagellar Biosynthesis Proteinmentioning
confidence: 99%